O que pode ser uma casa? A memória e a ressignificação da imagem através de experiências em artes visuais. - Andrade, Mel Taynná Brito Araújo (2021)
In “What can a house be? The memory and the reframing of the image through experiences in visual arts”, I present the research that aims at the analysis, experimentation and reflection of artistic actions that I made between 2019 and 2021 from my childhood house. I begin by introducing the house one-hundred-and-sixteen, the organization of the text, and the accompanying appendix items. I discuss what a house can be, considering this space as concrete and as an image, exploring works by artists such as Amanda Willians, Brígida Baltar, Diana Chiodelli, Do-Ho Suh, Hundertwasser and Yuri Firmeza; and theorists such as Bachelard, Brysson, Careri, Oliveira and Pallasmaa. I use art research (Salles, Zamboni) as a methodology to reflect on three artistic actions realized during the investigation: in “Life Simulation”, I deal with experiences with the electronic game The Sims 4 from the recreation of the one-hundred-and-sixteen in a virtual environment; in “RENT”, I narrate the path of investigation into the history of the house and its neighborhood, based on an urban action with street collages; in “The house that dwells in me”, I present the work in watercolor and drawing on issues surrounding memory and the imagined house. This investigation confirms the relevance of the house as an object of research and production in visual arts, whether as a theme or space for creation, by frequently linking the memories and subjectivities of the artists with the physical space.